Implementasi Destinasi Wisata Kuliner Berdasarkan Fatwa DSN MUI Nomor 108/DAN-MUI/X/2016 di Kota Bandung - Ghina Syifa Agustina; N. Eva Fauziah; Popon Srisusilawati (UNISBA Press, 2024)
Abstract. One of the MUI fatwas regarding tourism is contained in the Fatwa of the National Sharia Council of the Indonesian Ulema Council No. 108/DSN- MUI/X/2016. According to an article from Trip-Advisor, Indonesia's largest tourist reference social networking site also recommends